Perfluorooctanoic acid alters progesterone activity in human endometrial cells and induces reproductive alterations in young women. (March 2020) - Di Nisio, A.; Rocca, M.S.; Sabovic, I.; De Rocco Ponce, M.; Corsini, C.; Guidolin, D.; Zanon, C.; Acquasaliente, L.; Carosso, A.R.; De Toni, L.; Foresta, C.
Abstract: Female fecundity is finely regulated by hormonal signaling, representing a potential target for endocrine-disrupting chemicals. Among the chemicals of most concern are the perfluoroalkyl substances (PFAS), widely used in consumer goods, that are associated with adverse effects on reproductive health. In this context, the endometrium clearly represents an important fertility determining factor. The aim of this study was to investigate PFAS interference on hormonal endometrial regulation. This study was performed within a screening protocol to evaluate reproductive health in high schools. We studied a cohort of 146 exposed females aged 18–21 from the Veneto region in Italy, one of the four areas worldwide heavily polluted with PFAS, and 1080 non-exposed controls. In experiments on Ishikawa cells included UV–Vis spectroscopy, microarray analysis and qPCR. We report a significant dysregulation of the genetic cascade leading to embryo implantation and endometrial receptivity. The most differentially-expressed genes upon PFOA coincubation were ITGB8, KLF5, WNT11, SULT1E1, ALPPL2 and G0S2 (all p  < 0.01) . By qPCR, we confirmed an antagonistic effect of PFOA on all these genes, which was reversed at higher progesterone levels. Molecular interference of PFOA on progesterone was confirmed by an increase in the intensity of absorption spectra at 250 nm in a dose-dependent manner, but not in the presence of β-estradiol. Age at menarche (+164 days, p  = 0.006) and the frequency of girls with irregular periods (29.5% vs 21.5%, p  = 0.022) were significantly higher in the exposed group. Our results are indicative of endocrine-disrupting activity of PFAS on progesterone-mediated endometrial function. Highlights: PFAS could reduce female fecundity by interfering with hormonal pathways. PFOA shows consistent binding affinity for progesterone. Progesterone-activated genes in endometrial cells are dysregulated by PFOA. Age at menarche and irregular periods were higher in exposed young women.